Determination of trace element and fatty acid levels in tissues of mirror and scaly carp (Cyprinus carpio L., 1758) living in Keban Dam Reservoir (Elazig) - Aydin, Sevinc; Akkoyun, H. Turan; Akkoyun, Mahire Bayramoglu; Bengu, Aydin S.; Ekin, Suat; Harlioglu, Ayse G. (Wiley, 2022)
This study investigated the concentrations of some accumulated trace metals (iron, manganese, zinc and copper) and fatty acids in liver and muscle tissues of mirror and scaly carp varieties (Cyprinus carpio L., 1758) living in Keban Dam Reservoir (Elazig), which is the second-largest artificial lake in Turkey that hosts commercially valuable and preferred fish varieties for human consumption. The inductively coupled plasma mass spectrometry (ICP-MS) method was used to analyse the concentrations of trace elements. Fatty acid levels were measured in a gas chromatography mass spectrometry (GC-MS) device, using a flame ionization detector (FID). Considering the two fish varieties and tissues that were studied, the mean metal concentrations (mu g g(-1)) were found in the following ranges: Fe 12.32-49.97, Mn 0.12-0.62, Zn 10.45-86.59 and Cu 2.74-11.86. Although the lowest levels were detected in the muscle tissue for all the metals examined, the levels in the liver tissue were significantly higher. According to the results of the analyses on fatty acid concentrations, the mean total saturated fatty acid levels in the muscle tissue of the scaly carp and mirror carp varieties were found to be 31.07 and 31.43 (%), respectively, whereas these values for the liver tissue were consecutively 22.36 and 22.08 (%). Successively, the mean total levels of unsaturated fatty acids were determined as 68.93 and 68.40 (%) in the muscle tissue and 77.64 and 77.92 in the liver tissue. This study, with the finding that the trace (metallic) element accumulation rates were below the upper limits of the tolerable range, and the examined fish varieties were rich in fatty acids, shows that mirror carp and scaly carp living in Keban Dam Reservoir are highly nutritious for human diets.
Keywords: copper; Cyprinus Carpio; iron; manganese; metal element; zinc